2022
DOI: 10.3389/fpubh.2022.992959
|View full text |Cite
|
Sign up to set email alerts
|

Rational medication management mode and its implementation effect for the elderly with multimorbidity: A prospective cohort study in China

Abstract: BackgroundAs one of the countries with the most serious degree of aging, the incidence of potentially inappropriate drug use among the elderly is as high as 30. 4% in Chinese communities, and the lack of effective medication management and poor medication compliance at home are the main factors. Given these situations, we constructed a Rational Medication Management Mode based on family physician service, carried out an empirical research and evaluated the implementation effect.MethodsA prospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…In this study, it was not found that "health education" (17) and "whether to sign a contract with a family doctor" (18) were factors affecting the medication compliance of elderly people with multiple drugs in rural Hangzhou, which was different from the results of some studies (19)(20)(21). These ndings contribute to a better understanding of the relationship between drug use knowledge, drug use beliefs, and social support, and provide evidence for subsequent interventions to improve the status of multiple drug use in rural elderly groups.…”
Section: Discussioncontrasting
confidence: 87%
“…In this study, it was not found that "health education" (17) and "whether to sign a contract with a family doctor" (18) were factors affecting the medication compliance of elderly people with multiple drugs in rural Hangzhou, which was different from the results of some studies (19)(20)(21). These ndings contribute to a better understanding of the relationship between drug use knowledge, drug use beliefs, and social support, and provide evidence for subsequent interventions to improve the status of multiple drug use in rural elderly groups.…”
Section: Discussioncontrasting
confidence: 87%
“…However, they have low awareness and knowledge levels of rational drug use and poor understanding ability ( 25 ) and urgently require drug use knowledge. Therefore, it is suggested that relevant departments regularly organize pharmacists to conduct public lectures and seminars on rational drug use in rural areas and communities, distribute popular science books, provide medication consultation and guidance, follow up medication, and establish a chronic management center throughout the process, which can reduce the amount of multidrug use in elderly patients, reduce the incidence of multidrug use, enhance behavioral self-management, and increase knowledge and belief in rational drug use, eventually improving safety and medication adherence behavior ( 26 , 27 ). At the same time, these will constantly improve the overall quality of the science popularization team, establish a systematic and standardized science popularization system, provide a practical guarantee for promoting the widespread popularization of pharmacy science, promote the improvement of the scientific quality of safe drug use of residents, and actively help the implementation of the strategy of “Healthy China.”…”
Section: Discussionmentioning
confidence: 99%
“…For the independent variables, based on previous research results ( Jokanovic et al, 2015 ; Yang et al, 2015 ; Tang et al, 2021 ; Tang et al, 2022 ), we used age, living district (countryside or suburb or central-city), preference for medical institutions, number of visits (for community healthcare center, secondary hospital, and tertiary hospital, respectively), number of diagnoses, main types of disease as the eight risk factors.…”
Section: Methodsmentioning
confidence: 99%